Leaf reflectance and physiological attributes monitoring differentiate rice cultivars under drought-stress and non-stress conditions - Adjah, K.L.; Asante, M.D.; Frei, M.; Toure, A.; Aziadekey, M.; Wu, L.; Wairich, A.; Gamenyah,D.D.; Yadav, S. (2025)
rice production in africa is unambiguously hampered by drought. this study aimed to monitorthe efficiency of physiological traits (stomatal conductance (gsw), transpiration rate (e)), andleaf-reflectance (nDVi and rDVi) at vegetative (VS) and reproductive (rS) stages for selection ofdrought-tolerant genotypes. to achieve these objectives, we screened 14 rice genotypes underdrought-stress and non-stress conditions in the greenhouse. at VS-drought-stress, the relative-gswand relative-e consistently showed efficiency in differentiating drought-tolerant genotypes apoand Uplr-17 from the drought-sensitive ones at 11-, 18- and 27-days during VS-drought-stress,while nDVi, Cri1 and Cri2 at 18- and 27-days. at rS-drought-stress, genotypes apo and Uplr-17were selected as drought-tolerant genotypes based on the multi-trait-genotype-ideotype-distance-index (MGiDi) confirming the selection at 11-, 18- and 27-days during VS-drought-stress. this consistency in selecting apo and Uplr-17 as drought-tolerant genotypes at both VSand rS proved the efficiency of gsw, e, nDVi, rDVi, Cri1 and Cri2 in selecting for drought-tolerantvarieties at VS. Genotypes Uplr-17 and apo consistently showed homozygosity status for thefavorable alleles G, A, G and C for drought-tolerant Qtls DTY1.1 (snpOS00400), DTY1.1(snpOS00402), DTY1.1 (snpOS00408) and DTY12.1 (snpOS00483), respectively, confirming theirdrought tolerance status. at rS, with GYp recorded positive and significant correlation with rDVi,while regression analysis revealed that 34% of the variability in GYp is explained by rDVi. theregression analysis coupled with correlation analysis between lDS, DtF, rDVi and GYp impliedthat these traits can be used as predictors of GYp at rS-drought-stress. While gsw, e and nDViare recommended for monitoring during VS-drought-stress screening.